Thermometry of ultracold atoms via nonequilibrium work distributions - Johnson, T; Cosco, F; Mitchison, M; Jaksch, D; Clark, S (American Physical Society, 2016)
Estimating the temperature of a cold quantum system is difficult. Usually, one measures a wellunderstood thermal state and uses that prior knowledge to infer its temperature. In contrast, we introduce a method of thermometry that assumes minimal knowledge of the state of a system and is potentially non-destructive. Our method uses a universal temperature-dependence of the quench dynamics of an initially thermal system coupled to a qubit probe that follows from the Tasaki-Crooks theorem for non-equilibrium work distributions. We provide examples for a cold-atom system, in which our thermometry protocol may retain accuracy and precision at subnanokelvin temperatures.